Konstruksi Diri di Negeri Asing: Kajian Travel Writing Carl Thompson terhadap Pengalaman Tokoh Sri dalam Cerpen Rindu Menjelang Senja - Rusliawati, Ely; Wijianti, Ardia Septi (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
This study aims to analyse the short story Rindu Menjelang Senja by Raidah Athirah in the perspective of Carl Thompson's travel writing theory (2011) and postcolonial studies, focusing on three main aspects: Reporting the World, Revealing the Self, and Representing the Other. The method used is qualitative text analysis with a close reading approach to identify how diasporic narratives in this short story reflect identity negotiations between Indonesian (Eastern) and Polish (Western) cultures, as well as postcolonial power dynamics. The results show that this short story meets Thompson's travel writing criteria: (1) objective description of Poland (Reporting the World), such as snow weather and local customs; (2) expression of Sri's subjectivity as a diaspora (Revealing the Self), including the conflicts of adaptation and loneliness; and (3) ambiguous representation of Western culture (Representing the Other), the character does not explicitly criticise Polish domination but reveals inequality through personal experiences (for example, working as a nanny despite having a higher education). This analysis also reveals diasporic ambivalence through the concept of mimicry, Sri imitates Polish culture while missing Indonesia. This short story is a complex form of postcolonial travel writing, how diasporic identities are formed through constant negotiations between the self and the Other.